Vericiguat and Health-Related Quality of Life in Patients With Heart Failure With Reduced Ejection Fraction: Insights From the VICTORIA Trial - Butler, Javed; Stebbins, Amanda; Melenovský, Vojtěch; Sweitzer, Nancy K; Cowie, Martin R; Stehlik, Josef; Khan, Muhammad Shahzeb; Blaustein, Robert O; Ezekowitz, Justin A; Hernandez, Adrian F; Lam, Carolyn S P; Nkulikiyinka, Richard; et al. (Circulation. Heart failure, 2022)
BACKGROUND: We examined the effects of vericiguat compared with placebo in patients with heart failure with reduced ejection fraction enrolled in VICTORIA (Vericiguat Global Study in Patients With Heart Failure With Reduced Ejection Fraction) on health status outcomes measured by the Kansas City Cardiomyopathy Questionnaire (KCCQ) and evaluated whether clinical outcomes varied by baseline KCCQ score. METHODS: KCCQ was completed at baseline and 4, 16, and 32 weeks. We assessed treatment effect on KCCQ using a mixed-effects model adjusting for baseline KCCQ and stratification variables. Cox proportional-hazards modeling was performed to evaluate the effect of vericiguat on clinical outcomes by tertiles of baseline KCCQ clinical summary score (CSS), total symptom score (TSS), and overall summary score (OSS). RESULTS: Of 5050 patients, 4664, 4741, and 4470 had KCCQ CSS (median [25th to 75th], 65.6 [45.8-81.8]), TSS (68.8 [47.9-85.4]), and OSS (59.9 [42.0-77.1]) at baseline; 94%, 88%, and 82% had data at 4, 16, and 32 weeks. At 16 weeks, CSS improved by a median of 6.3 in both arms; no significant differences in improvement were seen for TSS and OSS between the 2 groups (P=0.69, 0.97, and 0.13 for CSS, TSS, and OSS). Trends were similar at 4 and 32 weeks. Vericiguat versus placebo reduced cardiovascular death or heart failure hospitalization risk similarly across tertiles of baseline KCCQ CSS, TSS, and OSS (interaction P=0.13, 0.21, and 0.65). CONCLUSIONS: Vericiguat did not significantly improve KCCQ scores compared with placebo. Vericiguat reduced the risk of cardiovascular death or heart failure hospitalization across the range of baseline health status. REGISTRATION: URL: https://www. CLINICALTRIALS: gov; Unique identifier: NCT02861534.
Keywords: Heart Failure; health status; Stroke Volume; heart failure; kvalita života; quality of life; lidé; srdeční selhání; pyrimidiny; heterocyklické sloučeniny bicyklické; Heterocyclic Compounds, 2-Ring; Quality of Life; Treatment Outcome; tepový objem; výsledek terapie; Pyrimidines; Humans